PENGARUH SOSIODRAMA TERHADAP KOMUNIKASI INTERPERSONAL SISWA DI SMA NEGERI 4 PEKANBARU TP 2016/2017 - Ramayanti, Febi; Umari, Tri; Arlizon, Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find out how the difference of students who are given sociodrama treatment with students who are not given sosiodrama treatment in SMA Negeri 4 Pekanbaru viewed from aspects of openness, empathy, positive attitude, supportive attitude, and equality. Aspects assessed in the process of sociodrama implementation of student interpersonal communication include participation, group dynamics, group atmosphere, and responding activities. In this research sociodrama activity is described in the form of scenario. Sosiodrama activities were conducted 5 times per experiment per group, all group members consisted of 45 students, 23 students for experiment group (ie 11 people in experimental group 1 and 12 people in experiment group 2) and 22 students for control group, 11 people in the control group 1 and 11 people in the control group 2. The level of interpersonal communication of students before the implementation of sociodrama entirely in the bad category that is with percentage of 100%, this happens because the entire subject of the selected study is in the bad category of as many as 23 people, While in the good category does not exist. After the implementation of sociodrama more than half of students are in good category that is equal to 91,3% while in very good category that is equal to 8,7% and bad category does not exist. So from the research results can be concluded that the influence of sociodrama to interpersonal communication that is 42.8% in the experimental group 1 and 50.6% in the experimental group 2 is in the strong category, so the sociodrama gives a positive influence on students' interpersonal communication.Keywords : Sociodrama, Interpersonal Communication